EFFECTIVENESS OF USING LANGUAGE LABORATORY IN TEACHING ENGLISH AMONG VII STANDARD STUDENTS IN COIMBATORE DISTRICT - Mercy, M. (International Journal of Research -GRANTHAALAYAH, 2016)
The present study is an attempt to study the effectiveness of using language laboratory in Teaching English among VII standard students in Coimbatore District. The sample consist of 64 students was taken up for the present study. Experimental method was used for the study. Collected data were analyzed. It is found that there is a significant means score difference between pre-test and post-test among the students. It proved that language laboratory supported positively when compared to traditional method. Teaching English through Language Laboratory is one of the appropriate and effective methods for teaching English.